If x = -3, calculate the value of the following expression:\(3x^{3} + (3x + 4) - 2x^{2}\)

-104

Explanation

To calculate the value of this expression, substitute -3 for x each time it appears in the expression: \(3(-3)^{3}+(3(-3)+4)-2(-3)^{2}\)

According to the order of operations, any operations inside of brackets must be done first: \(3(-3)^{3}+(-9+4)-2(-3)^{2}=3(-3)^{3}+-5-2(-3)^{2}\)

Then, the value of the expression can be calculated: 3(-27) + -5 - 2(9) =-81 + -5 – 18= -104

Visit our website for other ASVAB topics now!